Exercise and mitochondrial mechanisms in patients with sarcopenia - Alizadeh Pahlavani, Hamed; Laher, Ismail; Knechtle, Beat; Zouhal, Hassane (Frontiers in Physiology, 2022)
Sarcopenia is a severe loss of muscle mass and functional decline during aging that can lead to reduced quality of life, limited patient independence, and increased risk of falls. The causes of sarcopenia include inactivity, oxidant production, reduction of antioxidant defense, disruption of mitochondrial activity, disruption of mitophagy, and change in mitochondrial biogenesis. There is evidence that mitochondrial dysfunction is an important cause of sarcopenia. Oxidative stress and reduction of antioxidant defenses in mitochondria form a vicious cycle that leads to the intensification of mitochondrial separation, suppression of mitochondrial fusion/fission, inhibition of electron transport chain, reduction of ATP production, an increase of mitochondrial DNA damage, and mitochondrial biogenesis disorder. On the other hand, exercise adds to the healthy mitochondrial network by increasing markers of mitochondrial fusion and fission, and transforms defective mitochondria into efficient mitochondria. Sarcopenia also leads to a decrease in mitochondrial dynamics, mitophagy markers, and mitochondrial network efficiency by increasing the level of ROS and apoptosis. In contrast, exercise increases mitochondrial biogenesis by activating genes affected by PGC1-ɑ (such as CaMK, AMPK, MAPKs) and altering cellular calcium, ATP-AMP ratio, and cellular stress. Activation of PGC1-ɑ also regulates transcription factors (such as TFAM, MEFs, and NRFs) and leads to the formation of new mitochondrial networks. Hence, moderate-intensity exercise can be used as a non-invasive treatment for sarcopenia by activating pathways that regulate the mitochondrial network in skeletal muscle.